FOLFOX regimen after failure of fluorouracil and leucovorin plus nanoliposomal-irinotecan therapy for advanced pancreatic cancer: a retrospective observational study - Satoshi Kobayashi; Shun Tezuka; Yui Yamachika; Shotaro Tsunoda; Shuhei Nagashima; Yuichiro Tozuka; Taito Fukushima; Manabu Morimoto; Makoto Ueno; Junji Furuse; Shin Maeda (BMC Cancer, 2023)
Abstract Background Fluorouracil, leucovorin (5FU/LV), and nanoliposomal-irinotecan (nal-IRI) combination therapy has been established as the second-line treatment for advanced pancreatic ductal adenocarcinoma. Oxaliplatin with 5FU/LV (FOLFOX) is often used as a subsequent treatment, although its efficacy and safety are yet to be fully elucidated. We aimed to evaluate the efficacy and safety of FOLFOX as a third- or later-line treatment for patients with advanced pancreatic ductal adenocarcinoma. Methods We conducted a single-centre, retrospective study that enrolled 43 patients who received FOLFOX after failure of gemcitabine-based regimen followed by 5FU/LV + nal-IRI therapy between October 2020 and January 2022. FOLFOX therapy consisted of oxaliplatin (85 mg/m2), levo-leucovorin calcium (200 mg/m2) and 5-FU (2400 mg/m2) every 2 weeks per cycle. Overall survival, progression-free survival, objective response, and adverse events were evaluated. Results At the median follow-up time of 3.9 months in all patients, the median overall survival and progression-free survival were 3.9 months (95% confidence interval [CI], 3.1–4.8) and 1.3 months (95% CI, 1.0–1.5), respectively. Response and disease control rates were 0 and 25.6%, respectively. The most common adverse event was anaemia in all grades followed by anorexia; the incidence of anorexia and grades 3 and 4 was 21 and 4.7%, respectively. Notably, grades 3–4 peripheral sensory neuropathy was not observed. Multivariable analysis revealed that a C-reactive protein (CRP) level of > 1.0 mg/dL was a poor prognostic factor for both progression-free survival and overall survival: hazard ratios were 2.037 (95% CI, 1.010–4.107; p = 0.047) and 2.471 (95% CI, 1.063–5.745; p = 0.036), respectively. Conclusion FOLFOX as a subsequent treatment after failure of second-line treatment with 5FU/LV + nal-IRI is tolerable, although its efficacy is limited, particularly in patients with high CRP levels.